Hyperlipidemia that Induced in Male Rats and Role of Flavonoids Extract of Quercus infectoria in Treatment - Marwa Amer Shakir1, Iman Nozad Mahmood1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the study demonstrates flavonoids of Quercus infectoria as anti-hyperlipidemia. 20 adult male rats used and divided to four equal groups (each group consist 5 rats); rats received ad libidium, rats were given normal water containing 0.5% of hydrogen peroxide and 1% of cholesterol in the feed for 60 days for induction of hyperlipidemia. Hyperlipidemia rats treated with (50mg/kg/daily) flavonoids, fourth Hyperlipidemia rats treated with (100mg/kg/daily) flavonoids. The results show non-significant changes (P < 0.05) in levels of HMG-raductase compare with control group. in hyperlipidemia rats, levels of malonedialdehyied (MDA) show significant increase (P < 0.05) in and significant decrease (P < 0.05) in levels of glutathione (GSH) and catalase compare with control group. While, after using flavonoids extract in treatment, the results showed non-significant changes (P < 0.05) in HMG-raductase, MDA, GSH and catalase compare with control group. It was concluded that flavonoids extract of Q. infectoria extract has been a protective effect in rats with hyperlipidemia.